2021
DOI: 10.3390/min11080882
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Mechanical Properties of Paste Backfill with Flue-Gas Desulphurisation Gypsum under Combined Action of Dry–Wet Cycles and Chloride Erosion

Abstract: Flue-gas desulphurisation gypsum—a solid waste from power plants—can be used to prepare paste backfill for reducing costs. Most paste backfills are exposed to dry–wet cycles and chloride salt-rich water in mines. Therefore, the mechanical properties and damage mechanisms of paste backfill with desulphurised gypsum under the coupling action of erosion due to chloride with different concentrations and dry–wet cycles were investigated using methods such as visual observation, mass measurement, uniaxial compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Zhou et al [ 11 ] took cement-based composite materials as the test object, studied the changes in the physical and mechanical properties of specimens under the action of wet–dry cycles and found that long-term wet–dry cycles caused irreversible damage to cement-based composite materials. Wang et al [ 12 ] prepared a filling paste with cement, slag, desulfurized gypsum and other materials and studied the failure trends in the filling paste under the combined action of dry–wet cycles and chloride ions. Filling pastes remain immersed in mine water over long periods of time, and heavy metal ions present in the pastes may migrate to groundwater and cause environmental pollution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [ 11 ] took cement-based composite materials as the test object, studied the changes in the physical and mechanical properties of specimens under the action of wet–dry cycles and found that long-term wet–dry cycles caused irreversible damage to cement-based composite materials. Wang et al [ 12 ] prepared a filling paste with cement, slag, desulfurized gypsum and other materials and studied the failure trends in the filling paste under the combined action of dry–wet cycles and chloride ions. Filling pastes remain immersed in mine water over long periods of time, and heavy metal ions present in the pastes may migrate to groundwater and cause environmental pollution [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, binder inclusion ensures that the backfill becomes self-supporting after a short period, making the excavation of adjacent ore body possible. To ensure optimum performance of CPB, its early-age and long-term behaviors have to be incorporated in the design [7][8][9][10]. Some of these properties are responsible for its environmental performance (e.g., leachability, susceptibility to acid mine drainage) and are largely associated with hydraulic conductivity [11,12].…”
Section: Introductionmentioning
confidence: 99%